2013
DOI: 10.1089/neu.2012.2391
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Structural and Metabolic Changes in Traumatically Injured Hippocampus by Quantitative Differential Proteomics

Abstract: Traumatic brain injury (TBI) is a complex and common problem resulting in the loss of cognitive function. In order to build a comprehensive knowledge base of the proteins that underlie these cognitive deficits, we employed unbiased quantitative mass spectrometry, proteomics, and bioinformatics to identify and quantify dysregulated proteins in the CA3 subregion of the hippocampus in the fluid percussion model of TBI in rats. Using stable isotope 18 O-water differential labeling and multidimensional tandem liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…Thus, we hypothesized that changes in phosphorylation of residues at the FGF14 C-tail could affect the interaction with Nav channels. Our previous research has shown that GSK–3, a multifunctional kinase important for neuronal survival, cellular signaling, and stress response (Jope et al, 2007; Jope & Roh, 2006; Wu et al, 2013; Chen et al, 2011; Kim & Snider, 2011) and dysregulated in a number of AD and psychiatric disorders (Emamian, 2012; Jope et al, 2007; Jope & Roh, 2006; Liu et al, 2013; Budni et al, 2012; Scala et al, 2015; Maqbool et al, 2016; Morris & Berk, 2016; Provensi et al, 2016; Avila et al, 2010) affecting cognition, including depression and bipolar disorder (Gould et al, 2004; Koros & Dorner-Ciossek, 2007; Omata et al, 2011), critically modifies the interaction, assembly, localization, and activity of FGF14 and Nav channels (Hsu et al, 2015; James et al, 2015; Shavkunov et al, 2013). Furthermore, we observed that the C-tail of FGF14 contains a consensus GSK–3 phosphorylation motif ( S/T )XXX(S/T), the first residue in this sequence corresponding to S226.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesized that changes in phosphorylation of residues at the FGF14 C-tail could affect the interaction with Nav channels. Our previous research has shown that GSK–3, a multifunctional kinase important for neuronal survival, cellular signaling, and stress response (Jope et al, 2007; Jope & Roh, 2006; Wu et al, 2013; Chen et al, 2011; Kim & Snider, 2011) and dysregulated in a number of AD and psychiatric disorders (Emamian, 2012; Jope et al, 2007; Jope & Roh, 2006; Liu et al, 2013; Budni et al, 2012; Scala et al, 2015; Maqbool et al, 2016; Morris & Berk, 2016; Provensi et al, 2016; Avila et al, 2010) affecting cognition, including depression and bipolar disorder (Gould et al, 2004; Koros & Dorner-Ciossek, 2007; Omata et al, 2011), critically modifies the interaction, assembly, localization, and activity of FGF14 and Nav channels (Hsu et al, 2015; James et al, 2015; Shavkunov et al, 2013). Furthermore, we observed that the C-tail of FGF14 contains a consensus GSK–3 phosphorylation motif ( S/T )XXX(S/T), the first residue in this sequence corresponding to S226.…”
Section: Resultsmentioning
confidence: 99%
“…Stable isotope labeling was used to quantify differential phosphorylation between Tg2576 and Tg2576 on an RSG diet as previously described (Nenov et al, 2014; Sadygov et al, 2010; Wu et al, 2013). Briefly, the DG region of the hippocampus was dissected under magnification with a dissecting microscope, homogenized in TRIzol (Life Technologies), and resuspended in guanidine.…”
Section: Methodsmentioning
confidence: 99%
“…Differential Stable Isotope Labeling- 18 O/ 16 O differential stable isotope labeling was performed as described elsewhere (15)(16)(17)(18), with slight modifications. Briefly, 100 g each of HCV and HCC serum samples, both crude and ProteoMiner enriched, were denatured with 8 M GdmCl, reduced with 10 mM DTT for 30 min, alkylated with 30 mM iodoacetamide for 2 h at 37°C, digested with trypsin (1:50 enzymeto-protein ratio), diluted 10-fold with 50 mM ammonium bicarbonate, and incubated at 37°C for 24 h. Trypsin was deactivated by incubating samples at 95°C for 10 min and adding 12 l of 0.1% TFA to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Wu et al helps illustrate how profiling the proteomic response to TBI resolves ambiguity in interpreting results [37]. With one of the most comprehensive TBI proteome datasets published to date, Wu et al employed sophisticated informatic methods to identify calcineurin B1 (CANB1) as a central node in the down-regulation of the actin-tubulin structural network within injured hippocampus.…”
Section: Time As Critical Factor In Tbi Proteomic Studiesmentioning
confidence: 99%